Persistence of DNMT3A mutations at long‐term remission in adult patients with AML. (4th August 2014) - Pløen, Gro G.; Nederby, Line; Guldberg, Per; Hansen, Maria; Ebbesen, Lene H.; Jensen, Uffe Birk; Hokland, Peter; Aggerholm, Anni
Summary Mutations in DNMT3A, the gene encoding DNA methyltransferase 3 alpha, have been identified as molecular drivers in acute myeloid leukaemia (AML) with possible implications for minimal residual disease monitoring and prognosis. To further explore the utility of DNMT3A mutations as biomarkers for AML, we developed assays for sensitive detection of recurrent mutations affecting residue R882. Analysis of DNA from 298 diagnostic AML samples revealed DNMT3A mutations in 45 cases (15%), which coincided with mutations in NPM1, FLT3 and IDH1. DNMT3A mutations were stable in 12 of 13 patients presenting with relapse or secondary myelodysplastic syndrome, but were also present in remission samples from 14 patients (at allele frequencies of <1–50%) up to 8 years after initial AML diagnosis, despite the loss of all other molecular AML markers. The mutant DNMT3A allele burden was not related to the clinical course of disease. Cell sorting demonstrated the presence of DNMT3A mutations in leukaemic blasts, but also at lower allele frequencies in T and B‐cells from the same patients. Our data are consistent with the recent finding of preleukaemic stem cells in AML, which are resistant to chemotherapy. The persistence of DNMT3A mutations during remission may have important implications for the management of AML.